Research on Digitalization of the Museum Industry in China- Based on SWOT-PEST Model (Asian Journal of Social Science Studies, 2022)
As the main institution for the collection, the museum plays the role of collecting, publicity, education, and scientific research. It scientifically researches the collection, holds exhibitions, disseminates historical and scientific knowledge, providing the public with culture, education and appreciation services. The museum is a concentrated space of culture, contains human memory, and is a representative of the heritage and customs in a city, and even the country. With the development of technologies such as networks, the Internet of Things, digital and mobile communication, the application of high-tech in museums has continued to expand and deepen. Museums containing ancient civilizations are rejuvenated with the blood of new technology, presenting the long history to the public with a brand-new look, which become an unstoppable mainstream trend in the future. From the early “digital museums” to “smart museums” today, which has benefited from the development of science and technology. The integration of emerging technologies into museums, and the promoting the treasures of human civilization are by no means as simple as using technology to support them, which should start from a comprehensive and overall consideration. Therefore, this article starts from digitalization of the museum industry, uses the SWOT-PEST model as the analysis framework, and deeply explores the various factors in the development of museums in China, and discuss the strategic advice.